2002
DOI: 10.1523/jneurosci.22-09-03608.2002
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and Aging Affect the Subcellular Distribution of Estrogen Receptor-α in the Hippocampus of Female Rats

Abstract: Estrogen replacement increases both the number of dendritic spines and the density of axospinous synapses in the hippocampal CA1 region in young rats, yet this is attenuated in aged rats. The estrogen receptor-␣ (ER-␣) is localized within select spines of CA1 pyramidal cells in young animals and thus may be involved locally in this process. The present study investigated the effects of estrogen on the ultrastructural distribution of ER-␣ in the CA1 of young (3-4 months) and aged (22-23 months) Sprague Dawley r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
216
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 248 publications
(235 citation statements)
references
References 72 publications
18
216
1
Order By: Relevance
“…In the diencephalon, the change in ERα distribution in aging is not observed, but the immunostaining remains in the nuclei through the experiment in most cases, supporting some previous works (McEwen and Alves 1999;Ishunina et al 2000;Adams et al 2002). As it occurs in the telencephalon, ovariectomy makes the immunostaining decrease in an age-related way.…”
Section: Nuclear Location Of Erα (Arrows) Citoplasmmatic Location Ofsupporting
confidence: 85%
See 4 more Smart Citations
“…In the diencephalon, the change in ERα distribution in aging is not observed, but the immunostaining remains in the nuclei through the experiment in most cases, supporting some previous works (McEwen and Alves 1999;Ishunina et al 2000;Adams et al 2002). As it occurs in the telencephalon, ovariectomy makes the immunostaining decrease in an age-related way.…”
Section: Nuclear Location Of Erα (Arrows) Citoplasmmatic Location Ofsupporting
confidence: 85%
“…Furthermore, it was reported that not only is there an age regulation of the intensity of immunostaining, but also an evident influence of aging in the subcellular distribution of this receptor (Ishunina et al 2000;Milner et al 2001;Kalesnykas et al 2005). In ovariectomized animals, the effect of the sexual hormones in the ERα level and its localization within the cell, as is described by many researchers has also been widely demonstrated (Adams et al 2002;Wilson et al 2002;Stirone et al 2003).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations